Overt spatial attention modulates multisensory selection - Jensen, A; Frings, C; Spence, C; Merz, S (American Psychological Association, 2018)
In daily life, signals from the different senses are often integrated in order to enhance multisensory perception. However, an important, yet currently still controversial, topic con-cerns the need for attention in this integration process. To investigate this question, we turned to the processing of multisensory distractors. Note that multisensory target processing is typi-cally confounded with attention as people attend to the stimuli that they respond to. We therefore designed a multisensory flanker task in which the target and distractor stimuli were both multisensory and the congruency between the features (auditory and visual) was varied orthogonally. In addition, we manipulated whether distractor or target was within the focus of participants’ gaze (i.e., was overtly attended). Importantly, distractor congruency effects were modulated by this manipulation. Fixating the distractor led to crossmodal congruency effects between the visual and auditory feature dimensions (e.g., a visually incongruent distractor interfered more if it was also auditorily incongruent with the target), while congruency effects were independent of each other when the distractor was not fixated (i.e., visual interference was not modulated by auditory interference in this case). These results suggest that distractors outside the focus of overt attention are processed at the level of features whereas those dis-tractors presented centrally (i.e., at fixation) are processed as a configuration of features. Tak-en together, these results can be taken to suggest that the multisensory integration of irrelevant stimuli depends on the focus of spatial attention.